Immune Reconstitution and Graft-Versus-Host Reactions in Rat Models of Allogeneic Hematopoietic Cell Transplantation - Zinöcker, Severin; Dressel, Ralf; Wang, Xiao-Nong; Dickinson, Anne M.; Rolstad, Bent (Frontiers in Immunology, 2012)
Allogeneic hematopoietic cell transplantation (alloHCT) extends the lives of thousands of patients who would otherwise succumb to hematopoietic malignancies such as leukemias and lymphomas, aplastic anemia and disorders of the immune system. In alloHCT, different immune cell types mediate beneficial graft-versus-tumor (GvT) effects, regulate detrimental graft-versus-host disease (GvHD), and are required for protection against infections. Today, the ‘good’ (GvT effector cells and memory cells conferring protection) cannot be easily separated from the ‘bad’ (GvHD-causing cells), and alloHCT remains a hazardous medical modality. The transplantation of hematopoietic stem cells into an immunosuppressed patient creates a delicate environment for the reconstitution of donor blood and immune cells in co-existence with host cells. Immunological reconstitution determines to a large extent the immune status of the allo-transplanted host against infections and the recurrence of cancer, and is critical for long-term protection and survival after clinical alloHCT. Animal models continue to be extremely valuable experimental tools that widen our understanding of, for example, the dynamics of post-transplant hematopoiesis and the complexity of immune reconstitution with multiple ways of interaction between host and donor cells. In this review, we discuss the rat as an experimental model of HCT between allogeneic individuals. We summarize our findings on lymphocyte reconstitution in transplanted rats and illustrate the disease pathology of this particular model. We also introduce the rat skin explant assay, a feasible alternative to in vivo transplantation studies. The skin explant assay can be used to elucidate the biology of graft-versus-host reactions (GvHR), which are known to have a major impact on immune reconstitution, and to perform genome-wide gene expression studies using controlled combinations of minor and major histocompatibility between the donor and the recipient.